Akolẽ yethẽ Ākṭobara 1912 madhyẽ bharalelyā Sātavyā Mahārāshṭra-Sāhitya-Sammelanācā riporṭa, nibandha āṇi bhāshaṇẽ yãsaha (Mahārāshṭrasāhityaparishada, 1914)
Proceedings of the Seminar, articles and speeches studying Marathi literature.